The emerging role of circular RNAs in cisplatin resistance in ovarian cancer: From molecular mechanism to future potential - Mohaddese Malek Mohammadi; Hamidreza Rismanchi; Shakiba Esmailzadeh; Aryan Farahani; Neda Hedayati; Mina Alimohammadi; Alireza Mafi; Najma Farahani; Kiavash Hushmandi (Non-coding RNA Research)
Ovarian cancer (OC) is the most common cause of death in female cancers. The prognosis of OC is very poor due to delayed diagnosis and identification of most patients in advanced stages, metastasis, recurrence, and resistance to chemotherapy. As chemotherapy with platinum-based drugs such as cisplatin (DDP) is the main treatment in most OC cases, resistance to DDP is an important obstacle to achieving satisfactory therapeutic efficacy. Consequently, knowing the different molecular mechanisms involved in resistance to DDP is necessary to achieve new therapeutic approaches. According to numerous recent studies, non-coding RNAs (ncRNAs) could regulate proliferation, differentiation, apoptosis, and chemoresistance in many cancers, including OC. Most of these ncRNAs are released by tumor cells into human fluid, allowing them to be used as tools for diagnosis. CircRNAs are ncRNA family members that have a role in the initiation, progression, and chemoresistance regulation of various cancers. In the current study, we investigated the roles of several circRNAs and their signaling pathways on OC progression and also on DDP resistance during chemotherapy.